A positive electrode sheet, a method for manufacturing the same, and a high-energy-density long-life battery
Patent Information
- Application Number
- CN202510847534.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-06-23
- Publication Date
- 2026-10-20
AI Technical Summary
[0003]虽然overhang设计可以通过极片尺寸过量设计,提供电池的安全性能,但是会在一定程度上降低能量密度
[0029]本发明提供了一种正极片,包括集流体与设置于集流体至少一侧表面的涂层;所述涂层分为正极活性区、互渗区与导离子涂层区;所述正极活性区设置有正极活性层;所述导离子涂层区设置有导离子涂层;所述导离子涂层区位于正极片的边缘;所述互渗区为正极活性层与导离子涂层的渗透区域;所述正极活性区通过互渗区与导离子涂层区相接;所述导离子涂层包括5~20重量份的有机粘结剂、50~80重量份的纳米无机填料、5~25重量份的聚合物与0~15重量份的锂盐;所述聚合物为聚合物电解质的聚合物基体。与现有技术相比,本发明通过在正极片的边缘设置导离子涂层,其对电子绝缘,锂离子导通,可在负极脱锂的过程中为不与正极活性层重叠的负极区域的锂提供离子迁移通道,从而解决负极片边缘的析锂问题,同时提高电池的能量密度和循环寿命。
Smart Images

Figure BDA0005467082400000101 
Figure BDA0005467082400000102 
Figure BDA0005467082400000111
Abstract
Description
Technical Field
[0001] This invention belongs to the field of battery technology, and particularly relates to a positive electrode, its preparation method, and a high-energy-density, long-life battery. Background Technology
[0002] In the design process of lithium-ion batteries, the negative electrode is usually designed to extend beyond the positive electrode in both length and width. This design is usually called AC overhang design. It is mainly to reduce the difficulty of battery assembly and prevent lithium plating problems caused by the negative electrode not covering the positive electrode due to electrode misalignment.
[0003] While overhang designs can improve battery safety through excessive electrode size, they can reduce energy density to some extent. More seriously, overhang designs can affect battery capacity and cause lithium plating issues at the negative electrode edges, such as… Figure 1 As shown, during charging, some lithium ions diffuse laterally into the overhang region. During discharging, these lithium ions may not be able to completely return to the positive electrode, resulting in a decrease in discharge capacity. Although lithium ions in the overhang region may gradually diffuse back into the overlapping region with the increase in the number of cycles, under high current conditions, local excess lithium ions in both overlapping and non-overlapping regions can lead to edge lithium plating, ultimately affecting the cell's cycle life.
[0004] The current solution is to add a conventional ceramic coating to the top area of the positive electrode, such as... Figure 2 As shown, although it can improve the lithium plating problem of the negative electrode overhang to some extent, the ceramic layer itself does not have lithium conductivity and does not significantly improve the actual cycling performance. Summary of the Invention
[0005] In view of this, the technical problem to be solved by the present invention is to provide a positive electrode, its preparation method and a high energy density long life battery. The positive electrode can avoid the problem of lithium deposition at the edge of the negative electrode after multiple charge and discharge cycles caused by overhang design, thereby improving the overall performance of the battery.
[0006] This invention provides a positive electrode sheet, comprising a current collector and a coating disposed on at least one side surface of the current collector; the coating is divided into a positive electrode active region, an interpenetration region, and an ion-conducting coating region; the positive electrode active region is provided with a positive electrode active layer; the ion-conducting coating region is provided with an ion-conducting coating; the ion-conducting coating region is located at the edge of the positive electrode sheet; the interpenetration region is the area where the positive electrode active layer and the ion-conducting coating permeate; the positive electrode active region is connected to the ion-conducting coating region through the interpenetration region;
[0007] The ion-conducting coating comprises 5-20 parts by weight of an organic binder, 50-80 parts by weight of a nano-inorganic filler, 5-25 parts by weight of a polymer, and 0-15 parts by weight of a lithium salt; the polymer is a polymer matrix of a polymer electrolyte.
[0008] Preferably, the organic binder is selected from one or more of polyvinylidene fluoride, hydrogenated nitrile rubber, and polyvinyl butyral;
[0009] And / or, the nano-inorganic filler is selected from one or more of boehmite, silica, alumina, titanium dioxide and zirconium oxide;
[0010] And / or, the polymer is selected from one or more of polyethylene oxide, polyacrylonitrile, polymethyl methacrylate and polylactic acid;
[0011] And / or, the lithium salt is selected from lithium hexafluorophosphate and / or lithium bisfluorosulfonylimide.
[0012] Preferably, the width of the interpenetrating zone is d3.0 mm. <d3≤0.5mm;
[0013] And / or, the width of the ion-conducting coating region is d2, 1mm≤d2≤3mm.
[0014] Preferred, 0mm <d3≤0.2mm;
[0015] And / or, 1.5mm≤d2≤2.5mm.
[0016] Preferably, a positive electrode tab is provided on one side of the positive electrode sheet; the ion-conducting coating region is provided on the side of the positive electrode sheet where the positive electrode tab is provided and on the side opposite to the positive electrode tab.
[0017] Preferably, the thickness difference between the ion-conducting coating and the positive electrode active layer is controlled within 0 to 20 μm.
[0018] Preferably, the ion-conducting coating comprises 5-20 parts by weight of an organic binder, 50-80 parts by weight of a nano-inorganic filler, 5-25 parts by weight of a polymer, and 5-15 parts by weight of a lithium salt.
[0019] Preferably, the ion-conducting coating comprises 10-20 parts by weight of an organic binder, 50-70 parts by weight of a nano-inorganic filler, 15-25 parts by weight of a polymer, and 5-10 parts by weight of a lithium salt.
[0020] The present invention also provides a method for preparing the above-mentioned positive electrode, comprising the following steps:
[0021] S1) Organic binder, nano-inorganic filler, polymer and lithium salt are mixed in an organic solvent to obtain ion-conducting coating slurry;
[0022] S2) The ion-conducting coating slurry and the positive electrode slurry are coated on the surface of the current collector, and then dried and rolled to obtain the positive electrode sheet.
[0023] Preferably, step S1) specifically comprises:
[0024] A1) An organic binder, a polymer, and an organic solvent are mixed under heating conditions to obtain an intermediate slurry; the viscosity of the intermediate slurry is 10,000 to 20,000 mPa·s.
[0025] A2) The intermediate slurry, nano-inorganic filler and lithium salt are mixed and dispersed at high speed, and then an organic solvent is added to obtain an ion-conducting coating slurry; the viscosity of the ion-conducting coating slurry is 2000-8000 mPa·s.
[0026] Preferably, in step S2), the ion-conducting coating slurry is applied to the surface of the current collector by slit extrusion; the application speed is 5-30 m / min.
[0027] The present invention also provides a high energy density and long life battery, comprising the above-mentioned positive electrode, negative electrode and separator.
[0028] Preferably, the width of the overhang region of the negative electrode is d1; 0mm≤d1≤1mm.
[0029] This invention provides a positive electrode sheet, comprising a current collector and a coating disposed on at least one side of the current collector surface; the coating is divided into a positive electrode active region, an interpenetration region, and an ion-conducting coating region; the positive electrode active region is provided with a positive electrode active layer; the ion-conducting coating region is provided with an ion-conducting coating; the ion-conducting coating region is located at the edge of the positive electrode sheet; the interpenetration region is the penetration area between the positive electrode active layer and the ion-conducting coating; the positive electrode active region is connected to the ion-conducting coating region through the interpenetration region; the ion-conducting coating comprises 5-20 parts by weight of an organic binder, 50-80 parts by weight of a nano-inorganic filler, 5-25 parts by weight of a polymer, and 0-15 parts by weight of a lithium salt; the polymer is a polymer matrix of a polymer electrolyte. Compared with the prior art, this invention, by providing an ion-conducting coating at the edge of the positive electrode sheet, which is electronically insulated but allows lithium ions to conduct, can provide an ion migration channel for lithium in the negative electrode region that does not overlap with the positive electrode active layer during the lithium removal process of the negative electrode, thereby solving the lithium plating problem at the edge of the negative electrode sheet, and simultaneously improving the energy density and cycle life of the battery. Attached Figure Description
[0030] Figure 1 A schematic diagram illustrating the principle behind lithium plating issues arising from the negative electrode design for Overhang.
[0031] Figure 2 A schematic diagram illustrating the principle of applying a conventional ceramic coating to the overhang area;
[0032] Figure 3 This is a schematic diagram illustrating the principle of the positive electrode sheet used in this invention to solve the lithium plating problem at the negative electrode.
[0033] Figure 4 This is a schematic diagram of the electrode structure provided by the present invention;
[0034] Figure 5 This is a schematic cross-sectional view of the electrode sheet provided by the present invention. Detailed Implementation
[0035] The technical solutions of the present invention will be clearly and completely described below with reference to the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention.
[0036] This invention provides a positive electrode sheet, comprising a current collector and a coating disposed on at least one side surface of the current collector; the coating is divided into a positive electrode active region, an interpenetration region, and an ion-conducting coating region; the positive electrode active region is provided with a positive electrode active layer; the ion-conducting coating region is provided with an ion-conducting coating; the ion-conducting coating region is located at the edge of the positive electrode sheet; the interpenetration region is the permeation area between the positive electrode active layer and the ion-conducting coating; the positive electrode active region is connected to the ion-conducting coating region through the interpenetration region; the ion-conducting coating comprises 5-20 parts by weight of an organic binder, 50-80 parts by weight of nano-inorganic filler, 5-25 parts by weight of a polymer, and 0-15 parts by weight of a lithium salt; the polymer is a polymer matrix of a polymer electrolyte.
[0037] This invention solves the lithium plating problem at the edge of the negative electrode by setting an ion-conducting coating on the edge of the positive electrode sheet. This coating is insulated from electrons but allows lithium ions to pass through. During the lithium removal process of the negative electrode, it provides an ion migration channel for lithium in the negative electrode region that does not overlap with the positive electrode active layer, thereby improving the energy density and cycle life of the battery.
[0038] In this invention, the current collector can be any current collector well known to those skilled in the art, and there are no special limitations, including but not limited to aluminum foil.
[0039] In this invention, at least one side surface of the current collector is provided with a coating; the coating is divided into a positive electrode active region, an interpenetration region and an ion-conducting coating region.
[0040] Wherein, the positive electrode active region is the active region of the positive electrode sheet, preferably located in the middle region of the coating; the positive electrode active region is provided with a positive electrode active layer; the positive electrode active layer can be any positive electrode active layer well known to those skilled in the art, without any special limitations, and may specifically include a positive electrode active material, a positive electrode conductive agent, and a positive electrode binder; the positive electrode active material can be any positive electrode active material well known to those skilled in the art, without any special limitations, including but not limited to lithium cobalt oxide, lithium nickel cobalt manganese oxide, lithium iron phosphate, etc.; the positive electrode conductive agent can be any positive electrode conductive agent well known to those skilled in the art, without any special limitations, including but not limited to The positive electrode material comprises one or more of carbon black, graphite, conductive polymer, carbon nanotubes, and graphene; the positive electrode binder includes, but is not limited to, polyvinylidene fluoride (PVDF); the mass ratio of the positive electrode active material, the positive electrode conductive agent, and the positive electrode binder is preferably (95-99):(1-5):(0.1-2), more preferably (97-99):(1-3):(0.3-1.5), even more preferably (98-99):(1-2):(0.3-1), even more preferably (98-98.5):(1-1.5):(0.5-1), and most preferably 98.2:1.2:0.6.
[0041] In a specific embodiment provided by the present invention, the areal density of the positive electrode active layer is preferably 10-20 mg / cm³. 2 Optionally, the areal density of the positive electrode active layer is 10 mg / cm³. 2 11mg / cm 2 12mg / cm 2 13mg / cm 2 14mg / cm 2 15mg / cm 2 16mg / cm 2 17mg / cm 2 18mg / cm 2 19mg / cm 2 20mg / cm 2 Or the range between any two of the above values.
[0042] In one specific embodiment of the present invention, the compaction density of the positive electrode active layer is preferably 3.0–4.3 g / cm³. 3 Optionally, the areal density of the positive electrode active layer is 3.0 g / cm³. 3 3.2g / cm 3 3.5g / cm 3 3.8g / cm 3 4g / cm 3 4.2g / cm 3 4.3g / cm 3Or the range between any two of the above values.
[0043] In this invention, the ion-conducting coating region is located at the edge of the positive electrode, corresponding to a position where the negative electrode does not overlap with the positive electrode active region. During the delithiation process of the negative electrode, it can provide ion migration for lithium in this region, thereby solving the problem of lithium deposition at the edge of the negative electrode. A schematic diagram of its principle is shown below. Figure 3 As shown; in a specific embodiment of the present invention, a positive electrode tab is provided on one side of the positive electrode sheet, and the ion-conducting coating region is provided on the side of the positive electrode sheet where the positive electrode tab is provided and on the side opposite to the positive electrode tab. See [reference needed]. Figure 4 and Figure 5 , Figure 4 This is a schematic diagram of the electrode structure provided by the present invention. Figure 5 This is a schematic diagram of the cross-sectional structure of the electrode sheet provided by the present invention, wherein 4 is the positive electrode active region and the permeation region, 3 is the permeation region, 2 is the ion-conducting coating region, 1 is the overhang region, and 5 is the negative electrode sheet.
[0044] In one specific embodiment of the present invention, the width of the ion-conducting coating region is d2, where 1mm ≤ d2 ≤ 3mm; optionally, d2 is 1mm, 1.5mm, 2mm, 2.5mm, 3mm or any two of the above values.
[0045] In this invention, the width of the ion-conducting coating on the side with the positive electrode tab and the width of the ion-conducting coating on the opposite side can be the same or different. In a specific embodiment provided by this invention, the width of the ion-conducting coating on the side with the positive electrode tab and the width of the ion-conducting coating on the opposite side are the same.
[0046] In one specific embodiment of the present invention, the width of the ion-conducting coating region is d2, where 1.5mm≤d2≤2.5mm.
[0047] In one specific embodiment of the present invention, the thickness difference between the ion-conducting coating and the positive electrode active layer is preferably controlled within 0 to 20 μm; optionally, the thickness difference between the ion-conducting coating and the positive electrode active layer is controlled within the range of 0 μm, 2 μm, 4 μm, 6 μm, 8 μm, 10 μm, 12 μm, 14 μm, 16 μm, 18 μm, 20 μm or any two of the above values.
[0048] In a specific embodiment of the present invention, the thickness difference between the ion-conducting coating and the positive electrode active layer is preferably controlled within 0 to 5 μm.
[0049] In this invention, the ion-conducting coating comprises 5-20 parts by weight of an organic binder, 50-80 parts by weight of a nano-inorganic filler, 5-25 parts by weight of a polymer, and 0-15 parts by weight of a lithium salt; the polymer is a polymer matrix of a polymer electrolyte.
[0050] In one specific embodiment of the present invention, the organic binder may be any organic binder known to those skilled in the art, and there are no special limitations, including but not limited to one or more of polyvinylidene fluoride (PVDF), hydrogenated nitrile rubber (HNBR), and polyvinyl butyral (PVB); it mainly provides adhesion, so that other components in the ion-conducting coating adhere to each other and bond to the surface of the current collector.
[0051] In one specific embodiment of the present invention, the molecular weight of the organic binder is preferably 500,000 to 2,000,000; optionally, the molecular weight of the organic binder is 500,000, 800,000, 1,000,000, 1,200,000, 1,400,000, 1,600,000, 1,800,000, 2,000,000 or any two of the above values. In the embodiments provided by the present invention, PVDF5130 is specifically used as an example for illustration.
[0052] Optionally, the content of the organic binder in the ion-conducting coating is 5 parts by weight, 8 parts by weight, 10 parts by weight, 12 parts by weight, 15 parts by weight, 18 parts by weight, 20 parts by weight, or any two of the above values.
[0053] In one specific embodiment of the present invention, the nano-inorganic filler can be any nano-inorganic filler as described by those skilled in the art, and there are no special limitations, including but not limited to one or more of boehmite, silicon dioxide, alumina, titanium dioxide and zirconium oxide; the nano-inorganic filler can make the ion-conducting coating electronically insulating and can provide structural support.
[0054] Optionally, the content of the nano-inorganic filler in the ion-conducting coating is 50 parts by weight, 55 parts by weight, 60 parts by weight, 65 parts by weight, 70 parts by weight, 75 parts by weight, 80 parts by weight, or any two of the above values.
[0055] In one specific embodiment of the present invention, the polymer can be any polymer known to those skilled in the art that can be used as a polymer matrix in a polymer electrolyte, and there are no special limitations, including but not limited to one or more of polyethylene oxide (PEO), polyacrylonitrile (PAN), polymethyl methacrylate (PMMA), and polylactic acid (PLA); the polymer can enable the ion-conducting coating to have lithium-ion-conducting properties.
[0056] Optionally, the content of the polymer in the ion-conducting coating is 2 parts by weight, 5 parts by weight, 8 parts by weight, 10 parts by weight, 12 parts by weight, 15 parts by weight, 18 parts by weight, 20 parts by weight, 22 parts by weight, 25 parts by weight, or any two of the above values.
[0057] In one specific embodiment provided by the present invention, the weight-average molecular weight (M) of the polymer is... w Preferably, the weight-average molecular weight is between 100,000 and 1,000,000; optionally, the weight-average molecular weight of the polymer is 100,000, 200,000, 300,000, 400,000, 500,000, 600,000, 700,000, 800,000, 900,000, 1,000,000 or any two of the above values; in the embodiments provided by the present invention, M is used as... w Let's take a PEO of 600,000 as an example for explanation.
[0058] In one specific embodiment of the present invention, the lithium salt can be any lithium salt known to those skilled in the art, and there are no special limitations, including but not limited to lithium hexafluorophosphate (LiPF6) and / or lithium bisfluorosulfonylimide (LiFSI); adding lithium salt to the ion-conducting coating can act as a lithium conduction enhancer, further improving the ion conduction capability of the coating.
[0059] Optionally, the content of the lithium salt in the ion-conducting coating is 0 parts by weight, 2 parts by weight, 5 parts by weight, 8 parts by weight, 10 parts by weight, 12 parts by weight, 15 parts by weight, or any two of the above values.
[0060] In one specific embodiment of the present invention, the ion-conducting coating comprises 5-20 parts by weight of an organic binder, 50-80 parts by weight of a nano-inorganic filler, 5-25 parts by weight of a polymer, and 5-15 parts by weight of a lithium salt.
[0061] If the organic binder component in the ion-conducting coating is too small, the coating adhesion will be reduced, and if the polymer component is reduced, the ion-conducting properties of the coating will be reduced. Therefore, in a specific embodiment provided by the present invention, the ion-conducting coating includes 10 to 20 parts by weight of organic binder, 50 to 70 parts by weight of nano-inorganic filler, 15 to 25 parts by weight of polymer and 5 to 10 parts by weight of lithium salt. Within this range, the coating can have both good adhesion and good ion-conducting properties, thereby improving the energy density and cycle life of the battery cell.
[0062] In one specific embodiment of the present invention, the ion-conducting coating comprises 10 parts by weight of an organic binder, 70 parts by weight of a nano-inorganic filler, 15 parts by weight of a polymer, and 5 parts by weight of a lithium salt.
[0063] In a specific embodiment provided by the present invention, the ion-conductive coating comprises 10 parts by weight of an organic binder, 60 parts by weight of a nano inorganic filler, 20 parts by weight of a polymer, and 10 parts by weight of a lithium salt.
[0064] In a specific embodiment provided by the present invention, the ion-conductive coating comprises 20 parts by weight of an organic binder, 50 parts by weight of a nano inorganic filler, 25 parts by weight of a polymer, and 5 parts by weight of a lithium salt.
[0065] In a specific embodiment provided by the present invention, the ion-conductive coating comprises 5 parts by weight of an organic binder, 80 parts by weight of a nano inorganic filler, 10 parts by weight of a polymer, and 5 parts by weight of a lithium salt.
[0066] In a specific embodiment provided by the present invention, the ion-conductive coating comprises 10 parts by weight of an organic binder, 80 parts by weight of a nano inorganic filler, 5 parts by weight of a polymer, and 5 parts by weight of a lithium salt.
[0067] In a specific embodiment provided by the present invention, the ion-conductive coating comprises 10 parts by weight of an organic binder, 75 parts by weight of a nano inorganic filler, 15 parts by weight of a polymer, and 0 parts by weight of a lithium salt.
[0068] In the present invention, the positive electrode active region and the ion-conductive coating region are connected through an interpenetration region; the interpenetration region is a penetration region of the positive electrode active layer and the ion-conductive coating, that is, this region contains both the components of the positive electrode active layer and the components of the ion-conductive coating. The penetration region can reduce the difference of the positive electrode sheet coating and improve the ion-conductive performance of the coating.
[0069] In a specific embodiment provided by the present invention, the width of the interpenetration region is d3, 0mm<d3≤0.5mm; optionally, d3 is 0.01mm, 0.05mm, 0.08mm, 0.1mm, 0.2mm, 0.3mm, 0.4mm, 0.5mm, or a range between any two of the foregoing values.
[0070] In a specific embodiment provided by the present invention, the width of the interpenetration region is d3, 0mm<d3≤0.2mm.
[0071] In another specific embodiment provided by the present invention, the width of the interpenetration region is d3, 0mm<d3≤0.1mm.
[0072] The present invention further provides a preparation method of the above positive electrode sheet, comprising the following steps: S1) mixing an organic binder, a nano inorganic filler, a polymer and a lithium salt in an organic solvent to obtain an ion-conductive coating slurry; S2) coating the ion-conductive coating slurry and a positive electrode slurry on the surface of a current collector, followed by drying and rolling to obtain the positive electrode sheet.
[0073] In this invention, there are no special restrictions on the source of any raw materials; commercially available materials are acceptable. The types and proportions of the organic binder, nano-inorganic filler, polymer, and lithium salt are the same as described above and will not be repeated here.
[0074] An ion-conducting coating slurry is obtained by mixing an organic binder, nano-inorganic filler, polymer, and lithium salt in an organic solvent; the organic solvent can be any organic solvent known to those skilled in the art and is not particularly limited, including but not limited to N-methylpyrrolidone (NMP).
[0075] In a specific embodiment of the present invention, the above steps are as follows: A1) Mixing the organic binder, polymer and organic solvent under heating conditions to obtain an intermediate slurry; the viscosity of the intermediate slurry is 10000-20000 mPa·s; A2) Mixing the intermediate slurry, nano-inorganic filler and lithium salt, dispersing at high speed, and then adding an organic solvent to obtain an ion-conducting coating slurry; the viscosity of the ion-conducting coating slurry is 2000-8000 mPa·s.
[0076] An organic binder, polymer, and organic solvent are mixed under heating conditions to obtain an intermediate slurry; the mixing temperature is preferably 40℃~50℃; the mixing time is preferably 2~4h; optionally, the viscosity of the intermediate slurry is 10000mPa·s, 11000mPa·s, 12000mPa·s, 13000mPa·s, 14000mPa·s, 15000mPa·s, 16000mPa·s, 17000mPa·s, 18000mPa·s, 19000mPa·s, 20000mPa·s, or a range between any two of the above values.
[0077] The intermediate slurry, nano-inorganic filler, and lithium salt are mixed and dispersed at high speed, and then an organic solvent is added to obtain an ion-conducting coating slurry. The high-speed dispersion time is preferably 4 to 6 hours. Optionally, the viscosity of the ion-conducting coating slurry is 2000 mPa·s, 3000 mPa·s, 4000 mPa·s, 5000 mPa·s, 6000 mPa·s, 7000 mPa·s, 8000 mPa·s, or any two of the above values.
[0078] In one specific embodiment of the present invention, the ion-conducting coating slurry and the positive electrode slurry are simultaneously coated on the surface of the current collector; wherein the ion-conducting coating slurry forms an ion-conducting coating; and the positive electrode slurry forms a positive electrode active layer.
[0079] In one specific embodiment of the present invention, the ion-conducting coating slurry is preferably applied to the surface of the current collector by slit extrusion; the application speed is preferably 5 to 30 m / min; optionally, the application speed is 5 m / min, 10 m / min, 15 m / min, 20 m / min, 25 m / min, 30 m / min or any two of the above values.
[0080] In a specific embodiment of the present invention, the drying is preferably staged drying; the staged drying is preferably performed at 70℃~90℃, 110℃~130℃, and 140℃~160℃ in sequence, and more preferably at 80℃, 120℃, and 150℃ in sequence; the drying is preferably performed until the solvent residue is <0.1%.
[0081] In one specific embodiment of the present invention, the pressure of the roller pressing is preferably 10 to 20 MPa; optionally, the pressure of the roller pressing is 10 MPa, 12 MPa, 14 MPa, 16 MPa, 18 MPa, 20 MPa or any two of the above values.
[0082] The present invention also provides a high energy density and long life battery, comprising the above-mentioned positive electrode, negative electrode and separator.
[0083] In a specific embodiment of the present invention, the width d1 of the overhang region of the negative electrode sheet is 0mm ≤ d1 ≤ 1mm; the overhang region refers to the region of the negative electrode sheet that does not overlap with the positive electrode sheet; optionally, the width of d1 is 0mm, 0.1mm, 0.2mm, 0.3mm, 0.4mm, 0.5mm, 0.6mm, 0.7mm, 0.8mm, 0.9mm, 1mm or any two of the above values.
[0084] In one specific embodiment of the present invention, the width of the overhang region of the negative electrode is d1; d1 is 0 mm.
[0085] In a specific embodiment of the present invention, the negative electrode sheet includes a negative electrode current collector and a negative electrode active layer disposed on at least one side surface of the negative electrode current collector; the negative electrode current collector can be any negative electrode current collector well known to those skilled in the art, and there are no special limitations, including but not limited to copper foil; the negative electrode active layer includes a negative electrode active material, a negative electrode conductive agent, and a negative electrode binder; the negative electrode active material can be any negative electrode active material well known to those skilled in the art, and there are no special limitations, including but not limited to one or more of carbon-based compounds, silicon-based compounds, titanium-based compounds, alloy materials, and transition metal compounds; the carbon-based compounds include but are not limited to one or more of soft carbon, hard carbon, and graphite; the silicon-based compounds include but are not limited to silicon nanomaterials, silicon-carbon composite materials, etc.; the titanium-based compounds include but are not limited to titanium dioxide, lithium titanate, etc.; the alloy materials include but are not limited to Al, Sn, Mg, Ag, Sb, etc.; the transition metal compounds include but are not limited to transition metal oxides, transition metal sulfides, transition metal phosphides, etc.; the transition metal oxide MO x (M represents Fe, Co, Ni, Cu, Zn, etc.); the transition metal sulfides include, but are not limited to, copper sulfide, molybdenum sulfide, cobalt sulfide, iron sulfide, etc.; the transition metal phosphides include, but are not limited to, phosphides of nickel, cobalt, copper, iron, aluminum, etc.; the negative electrode conductive agent can be any conductive agent well known to those skilled in the art, and there are no special limitations. In this invention, it includes, but is not limited to, one or more of carbon black, graphite, conductive polymers, carbon nanotubes, graphene, etc.; the negative electrode binder includes, but is not limited to, styrene-butadiene rubber (SBR). SBR) and / or sodium carboxymethyl cellulose (CMC); the mass ratio of the negative electrode active material, the negative electrode conductive agent and the negative electrode binder is preferably (95-99):(0.1-2):(1-5), more preferably (95-98):(0.3-1.5):(1-3), even more preferably (96-97):(0.3-1):(2-3), even more preferably (96.5-97):(0.3-0.8):(2.5-3), and most preferably 96.8:0.5:2.7.
[0086] In one specific embodiment of the present invention, the diaphragm can be any diaphragm known to those skilled in the art, and there are no special limitations, including but not limited to polypropylene (PP) and / or polyethylene (PE), single-sided coated diaphragms, etc.
[0087] In one specific embodiment of the present invention, the battery further includes an electrolyte; the electrolyte can be any electrolyte well known to those skilled in the art, and there are no special limitations, specifically including lithium salts, solvents and additives.
[0088] Wherein, the lithium salt can be any lithium salt well known to those skilled in the art, and there are no special limitations, including but not limited to one or more of lithium hexafluorophosphate, lithium bis(fluorosulfonyl)imide, lithium fluorosulfonyl (perfluorobutylsulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide, lithium tetrafluoroborate, lithium perchlorate, lithium hexafluoroarsenate, lithium bis(oxalate-borate), lithium difluorooxalate-borate, lithium trifluoromethanesulfonate, and lithium tetrafluorooxalate phosphate; the concentration of the lithium salt in the electrolyte is preferably 0.5 to 2 mol / L; optionally, the concentration of the lithium salt in the electrolyte is 0.5 mol / L, 0.8 mol / L, 1 mol / L, 1.2 mol / L, 1.5 mol / L, 2 mol / L, or any two of the above values.
[0089] The solvent can be any solvent known to those skilled in the art that can be used as an electrolyte, and there are no special limitations. It includes, but is not limited to, one or more of ethylene carbonate (EC), ethyl methyl carbonate (EMC), dimethyl carbonate (DMC), propane sulfonate lactone (PS), propyl propionate (PP), and methyl propionate (EP). In the embodiments provided by the present invention, ethylene carbonate (EC), ethyl methyl carbonate (EMC), propyl propionate (PP), and methyl propionate (EP) in a volume ratio of 20%:40%:15%:25% are used as an example for illustration.
[0090] The additive can be any electrolyte additive well known to those skilled in the art, and there are no special limitations, including but not limited to one or more of vinylene carbonate (VC), fluoroethylene carbonate (FEC), lithium difluorophosphate (LiPO2F2), adiponitrile (AND), and hexanetrionitrile (HTCN); the mass of the additive is preferably 0.1% to 5% of the electrolyte mass; optionally, the mass of the additive is 0.1%, 0.5%, 1%, 2%, 3%, 4%, 4.5%, 5% of the electrolyte mass or a range between any two of the above values.
[0091] This application also provides an electrical device, including the battery described above.
[0092] In specific applications, electrical equipment can include laptops, pen-based computers, mobile computers, e-book players, portable telephones, portable fax machines, portable copiers, portable printers, stereo headphones, video recorders, LCD TVs, portable cleaners, portable CD players, mini CDs, transceivers, electronic notebooks, calculators, memory cards, portable recorders, radios, backup power supplies, motors, automobiles, motorcycles, electric bicycles, bicycles, ships, spacecraft, lighting fixtures, toys, game consoles, clocks, power tools, flashlights, cameras, large household batteries, and lithium-ion capacitors, etc.
[0093] Specifically, the vehicles can be gasoline-powered vehicles, natural gas-powered vehicles, or new energy vehicles. New energy vehicles can be pure electric vehicles, hybrid electric vehicles, or range-extended electric vehicles, etc.
[0094] To further illustrate the present invention, the following describes in detail, in conjunction with embodiments, a positive electrode sheet provided by the present invention, its preparation method, and a high-energy-density, long-life battery.
[0095] All reagents used in the following examples are commercially available.
[0096] Examples 1-6 and Comparative Examples 1-3
[0097] Step 1) Slurry preparation:
[0098] Weigh organic component 1 and organic component 2 according to the mass ratio in Table 1, dissolve them in NMP, and stir until completely dissolved and dispersed (45℃, 2h). The viscosity range is controlled at 15000±1000mPa·s.
[0099] After a uniform dispersion is formed, inorganic component 1 and inorganic component 2 are added according to the proportions in the example and dispersed at high speed for 5 hours. Then, NMP is added until the slurry viscosity is 4000±1000 mPa·s to obtain the ion-conducting coating slurry.
[0100] Step S2) Coating, drying, and rolling process:
[0101] The ion-conducting coating slurry is applied using a slit extrusion coating method at a speed of 30 m / min, and is carried out simultaneously with the coating of the main positive electrode slurry.
[0102] Segmented drying (80℃→120℃→150℃), solvent residue <0.1%.
[0103] The rolling pressure is 20MPa, and the final thickness of the ion-conducting coating is controlled to be similar to that of the positive electrode material layer. The difference between the thickness of the ion-conducting coating and the thickness of the positive electrode is in the range of 0 to 5μm.
[0104] The cathode material is 4.48V lithium cobalt oxide, with an active material content of 98.2%. The mass ratio of cathode material, conductive carbon black (SP), conductive carbon nanotubes (CNTs), and binder PVDF is 98.2:0.4:0.8:0.6. The areal density of the cathode coating is 15.3 mg / cm³. 2 The positive electrode compaction density is 4.05 g / cm³. 3 The positive electrode is prepared into a positive electrode sheet by means of slurry coating and drying, according to the examples and comparative examples.
[0105] Step S3) Assemble the battery:
[0106] The negative electrode material is selected from Shanshan 5C fast-charging graphite, with an active material content of 96.8%. The mass ratio of the negative electrode material, conductive agent carbon black SP, binder lithium carboxymethyl cellulose (CMC-Li), and binder styrene-butadiene rubber (SBR) is 96.8:0.5:1.2:1.5, and the anode sheet density is 6.2 mg / cm³. 2 The negative electrode compaction density is 1.60 g / cm³. 3 ;
[0107] Except for Comparative Example 3, the positive and negative electrode sheets are of equal size. The ion-conducting coating is disposed on one side of the positive electrode tab and the side opposite to the positive electrode tab of the positive electrode sheet. The width of the ion-conducting coating on one side is 2mm±0.5mm, and the interpenetration zone is controlled to be 0.1~0.2mm. The AC overhang on one side of the positive and negative electrodes in Comparative Example 4 is designed to be 2mm±0.5mm.
[0108] The electrolyte uses a conventional 5C fast-charging electrolyte, 1M LiPF6, with solvents of ethylene carbonate (EC): ethyl methyl carbonate (EMC): propyl propionate (PP): methyl propionate (EP) = 20%: 40%: 15%: 25%, and additives of 0.5% vinylene carbonate (VC) + 1% fluoroethylene carbonate (FEC) + 1% lithium difluorophosphate (LiPO2F2) + 0.5% adiponitrile (AND) + 1.5% hexanetrionitrile (HTCN).
[0109] The separator uses a 5μm PE base membrane, a 2μm burr stone, and a 1μm PVDF adhesive layer on each side; the ceramic side faces the positive electrode plate side.
[0110] The full battery has a design capacity of 5100mAh. It was subjected to 5C stepped charging at room temperature and 45℃ high temperature cycling, including 800 cycles at room temperature and 600 cycles at high temperature. The results are shown in Table 2.
[0111] The soft-pack charging and discharging process is as follows: 5C constant current charging (CC) to 4.15V, 4C constant current charging (CC) to 4.2V, 3C constant current charging (CC) to 4.3V, 2C constant current constant voltage charging (CC-CV) to 4.4V, 0.05C cutoff, rest for 10 minutes;
[0112] Charge at 1C constant current (CC) to 3.0V, charge at 0.5C constant current (CC) to 3.0V, and rest for 10 minutes.
[0113] Table 1 Composition of Ion-Conducting Slurry
[0114]
[0115] Table 2 Battery performance test results
[0116]
[0117]
[0118] As shown in Table 2, setting an ion-conducting coating containing specific components at the edge of the positive electrode to reduce or eliminate the overhang area of the negative electrode can improve the energy density and cycle life of the battery.
[0119] The above description is only a preferred embodiment of the present invention. It should be noted that for those skilled in the art, several improvements and modifications can be made without departing from the principle of the present invention, and these improvements and modifications should also be considered within the scope of protection of the present invention.
Claims
1. A positive electrode plate, characterized in that, The device includes a current collector and a coating disposed on at least one side of the current collector surface; the coating is divided into a positive electrode active region, an interpenetration region, and an ion-conducting coating region; the positive electrode active region is provided with a positive electrode active layer; the ion-conducting coating region is provided with an ion-conducting coating; the ion-conducting coating region is located at the edge of the positive electrode sheet; the interpenetration region is the area where the positive electrode active layer and the ion-conducting coating permeate; the positive electrode active region is connected to the ion-conducting coating region through the interpenetration region; The ion-conducting coating comprises 5-20 parts by weight of an organic binder, 50-80 parts by weight of a nano-inorganic filler, 5-25 parts by weight of a polymer, and 0-15 parts by weight of a lithium salt; the polymer is a polymer matrix of a polymer electrolyte.
2. The positive electrode sheet according to claim 1, characterized in that, The organic binder is selected from one or more of polyvinylidene fluoride, hydrogenated nitrile rubber and polyvinyl butyral; And / or, the nano-inorganic filler is selected from one or more of boehmite, silica, alumina, titanium dioxide and zirconium oxide; And / or, the polymer is selected from one or more of polyethylene oxide, polyacrylonitrile, polymethyl methacrylate and polylactic acid; And / or, the lithium salt is selected from lithium hexafluorophosphate and / or lithium bisfluorosulfonylimide.
3. The positive electrode sheet according to claim 1, characterized in that, The width of the interpenetrating zone is d3.0 mm. <d3≤0.5mm; And / or, the width of the ion-conducting coating region is d2, 1mm≤d2≤3mm.
4. The positive electrode sheet according to claim 3, characterized in that, 0mm <d3≤0.2mm; And / or, 1.5mm≤d2≤2.5mm.
5. The positive electrode sheet according to claim 1, characterized in that, A positive electrode tab is provided on one side of the positive electrode sheet; the ion-conducting coating region is provided on the side of the positive electrode sheet where the positive electrode tab is provided and on the side opposite to the positive electrode tab.
6. The positive electrode sheet according to claim 1, characterized in that, The thickness difference between the ion-conducting coating and the positive electrode active layer is controlled within 0–20 μm.
7. The positive electrode sheet according to claim 1, characterized in that, The ion-conducting coating comprises 5-20 parts by weight of an organic binder, 50-80 parts by weight of a nano-inorganic filler, 5-25 parts by weight of a polymer, and 5-15 parts by weight of a lithium salt.
8. The positive electrode sheet according to claim 1, characterized in that, The ion-conducting coating comprises 10-20 parts by weight of an organic binder, 50-70 parts by weight of a nano-inorganic filler, 15-25 parts by weight of a polymer, and 5-10 parts by weight of a lithium salt.
9. A method for preparing a positive electrode sheet according to any one of claims 1 to 8, characterized in that, Includes the following steps: S1) Organic binder, nano-inorganic filler, polymer and lithium salt are mixed in an organic solvent to obtain ion-conducting coating slurry; S2) The ion-conducting coating slurry and the positive electrode slurry are coated on the surface of the current collector, and then dried and rolled to obtain the positive electrode sheet.
10. The preparation method according to claim 9, characterized in that, Step S1) specifically involves: A1) An organic binder, a polymer, and an organic solvent are mixed under heating conditions to obtain an intermediate slurry; the viscosity of the intermediate slurry is 10,000 to 20,000 mPa·s. A2) The intermediate slurry, nano-inorganic filler and lithium salt are mixed and dispersed at high speed, and then an organic solvent is added to obtain an ion-conducting coating slurry; the viscosity of the ion-conducting coating slurry is 2000-8000 mPa·s.
11. The preparation method according to claim 9, characterized in that, In step S2), the ion-conducting coating slurry is applied to the surface of the current collector by slit extrusion; the application speed is 5-30 m / min.
12. A high-energy-density, long-life battery, characterized in that, It includes the positive electrode sheet as described in any one of claims 1 to 8 or the positive electrode sheet, negative electrode sheet and separator prepared by any one of claims 9 to 11.
13. The high energy density, long lifespan battery according to claim 12, characterized in that, The width of the overhang region of the negative electrode is d1; 0mm≤d1≤1mm.